Sorting out Neighbourhood Effects Using Sibling Data - Lina Hedman; David Manley; Maarten van Ham (Institute of Labor Economics (IZA), 2017)
Previous research has reported evidence of intergenerational transmission of both neighbourhood status and social and economic outcomes later in life; parents influence where their children live as adults and how well they do later in life in terms of their income. However, interactions between the individual, the childhood family and neighbourhood context and the neighbourhood experiences after leaving the parental home are often overlooked which might bias estimates of neighbourhood effects. It is likely that part of the effects attributed to neighbourhoods, are actually effects of the family in which someone was brought up. This study uses a sibling design to disentangle family and neighbourhood effects on income, and synthetic sibling pairs are used as a control group. The sibling design allows us to separate the effects of childhood family and neighbourhood contexts, but also between childhood neighbourhood effects and effects of the adult neighbourhood experiences. Using data from Swedish registers we show that the neighbourhood effect from both childhood and adult neighbourhood exposure is biased upwards by the influence of the family context. This leads to the conclusion that part of what appeared to be a neighbourhood effect was in fact a lasting family effect. Interestingly, we find that there is a long lasting effect of the family context on income later in life, and that this effect is strong regardless the individual neighbourhood pathway later in life.
Keywords: I30; J60; R23; 330; siblings; non-random sorting; neighbourhood effects; family; income; longitudinal data